A nutritional supplement taken during preconception and pregnancy influences human milk macronutrients in women with overweight/obesity and gestational diabetes mellitus - Han, Soo Min; Derraik, José G. B.; Vickers, Mark H.; Devaraj, Surabhi; Huang, Fang; Pang, Wei Wei; Godfrey, Keith M.; Chan, Shiao-Yng; Thakkar, Sagar K.; Cutfield, Wayne S.; , NiPPeR Study Group; Albert, Benjamin B.; et al. (Frontiers in Nutrition, 2023)
Rational Maternal overweight/obesity and gestational diabetes mellitus (GDM) are associated with an increased risk of their offspring developing overweight/obesity or type 2 diabetes later in life. However, the impact of maternal overweight/obesity and dysglycemia on human milk (HM) macronutrient composition is not well understood.Objective Through a double-blind randomized controlled trial, we investigated the effects of maternal supplementation from preconception throughout pregnancy until birth on HM macronutrient concentrations, in association with maternal and infant factors including maternal pre-pregnancy body mass index (BMI) and GDM status. In addition, we aimed to characterize longitudinal changes in HM macronutrients.The control supplement contained calcium, iodine, iron, β-carotene, and folic acid. The intervention supplement additionally contained zinc, vitamins B2, B6, B12, D3, probiotics and myoinositol. HM samples were collected across 7 time points from 1 week to 12 months from Singapore and New Zealand. HM macronutrient concentrations were measured using a MIRIS Human Milk Analyser. Potential differences in HM macronutrient concentrations were assessed using linear mixed models with a repeated measures design.Overall, HM macronutrient concentrations were similar between control and intervention groups. Among the control group, overweight/obesity BMI and GDM were associated with higher HM fat and energy concentrations over the first 3 months. Such associations were not observed among the intervention group. Of note, mothers with GDM in the intervention group had lower HM fat by 10% (p=0.049) and energy by 6% (p=0.029) than mothers with GDM in the control group. Longitudinal changes in HM macronutrient concentrations over 12 months of lactation in New Zealand showed that HM fat and energy decreased in the first 6 months then increased until 12 months. HM lactose and crude protein gradually decreased from 1 week to 6 months then remained relatively constant until 12 months.Conclusions Maternal overweight/obesity or GDM were associated with increased HM fat and energy levels. We speculate the intervention taken during preconception and pregnancy altered the impact of maternal BMI or GDM status on HM macronutrient composition. Further studies are required to identify the mechanisms underlying altered HM macronutrient concentration and to determine any long-term effects on offspring health.